Mengenal Paradigma Penelitian Pendidikan - Rumina; pengelola, pengelola (TABYIN: JURNAL PENDIDIKAN ISLAM, 2023)
Research is a structured and systematic process that requires certain stages and steps to carry it out. By using systematic patterns or stages, the research process can be followed by others more easily. The research paradigm is a frame of mind that explains how researchers view the facts of social life, researchers towards science and theory, which are constructed as a fundamental view of a scientific discipline about what is the subject matter that should be studied. Paradigm is seen as an important thing because of its ability to dissect empirical reality and its flexibility in addressing the problem to be solved. In other words, a paradigm is a point of view that is used to understand a phenomenon correctly. The type of research paradigm, namely Qualitative Research, is a research method that is more focused on understanding social phenomena from the perspective of participants by focusing more on a more complete picture rather than breaking down into interrelated variables. And Quantitative Research is a descriptive research method and uses more analysis. Quantitative research aims to find relationships that explain causes in measurable social facts, show variable relationships and analyze them